Influência dos períodos e posições de armazenamento sobre o tipo de brotação, diâmetro do pseudocaule, número de folhas e altura das plantas de bananeira (Musa cavendishii Lambert) cv "Nanicão" - Manica, Ivo; Simão , Salim; Bezerra Fernandes , Mário (Revista Ceres, 2025)
The effect of time and storage position of banana planting material on the development of banana (Musa cavendiehit Lambert) cv. 'Nanicão') was studied in Piracicaba, São Paulo. None of the treatments significantly influenced leaf number or pseudostem circumference. The best results in terms of plant height were obtained by planting material without storage. There was a marked correlation between the position of the planting material and the point of origin of the suckers. All treatments attained greater plant height of planting material with apical growth.